PENGARUH VARIASI LATIHAN SERANGAN TERHADAP KETEPATAN TUSUKAN ATLET ANGGAR PROVINSI JAMBI - Rasyono Rasyono; Grafitte Decheline (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2019)
Fencing is one sport that is competed to international events such as the World Championship to the Olympics. To improve the achievement of fencing athletes in Jambi Province who are still in the poor category, it is necessary to provide appropriate exercises and according to the needs of athletes. The problem in this study is whether there is an effect of attack training on the accuracy of the Jambi Province Fencing athlete puncture. The research method used was an experiment with the Pre test Post test design method. The sample in the study were 10 people. The results of the study are acceptable hypotheses, namely the effect of attack training on the accuracy of the fencing athlete puncture, with a significance of 5% and the results of the normality test are Lo <= Ltabel because Lo = 0,0009 and Ltabel = 0,220 then Ho is accepted. There is an increase of around 1.1% as a result of puncture accuracy from the results of the pre-test and post-test. Keywords: Fencing, Attack, Accuracy, puncture